Extraction of Curcumin Pigment from Indonesian Local Turmeric with Its Infrared Spectra and Thermal Decomposition Properties. (March 2017) - Nandiyanto, A B D; Wiryani, A S; Rusli, A; Purnamasari, A; Abdullah, A G; Ana,; Widiaty, I; Hurriyati, R
Abstract: Curcumin is one of the pigments which is used as a spice in Asian cuisine, traditional cosmetic, and medicine. Therefore, process for getting curcumin has been widely studied. Here, the purpose of this study was to demonstrate the simple method for extracting curcumin from Indonesian local turmeric and investigate the infrared spectra and thermal decomposition properties. In the experimental procedure, the washed turmeric was dissolved into an ethanol solution, and then put into a rotary evaporator to enrich curcumin concentration. The result showed that the present method is effective to isolate curcumin compound from Indonesian local turmeric. Since the process is very simple, this method can be used for home industrial application. Further, understanding the thermal decomposition properties of curcumin give information, specifically relating to the selection of treatment when curcumin must face the thermal-related process.